2016
DOI: 10.1093/mnras/stw3195
|View full text |Cite
|
Sign up to set email alerts
|

A dynamical model for gas flows, star formation and nuclear winds in galactic centres

Abstract: We present a dynamical model for gas transport, star formation, and winds in the nuclear regions of galaxies, focusing on the Milky Way's Central Molecular Zone (CMZ). In our model angular momentum and mass are transported by a combination of gravitational and bar-driven acoustic instabilities. In gravitationally-unstable regions the gas can form stars, and the resulting feedback drives both turbulence and a wind that ejects mass from the CMZ. We show that the CMZ is in a quasi-steady state where mass deposite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
128
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 111 publications
14
128
1
Order By: Relevance
“…In Paper I, we showed that star formation mostly takes place within the dense ring-like structure, and that is characterised by oscillatory cycles of burst/quenching. Our simulations suggest that the current CMZ is near a minimum of a star formation cycle, in agreement with the findings of earlier analytic and one-dimensional dynamical models by Kruijssen et al (2014), Krumholz & Kruijssen (2015), and Krumholz et al (2017).…”
Section: Introductionsupporting
confidence: 91%
“…In Paper I, we showed that star formation mostly takes place within the dense ring-like structure, and that is characterised by oscillatory cycles of burst/quenching. Our simulations suggest that the current CMZ is near a minimum of a star formation cycle, in agreement with the findings of earlier analytic and one-dimensional dynamical models by Kruijssen et al (2014), Krumholz & Kruijssen (2015), and Krumholz et al (2017).…”
Section: Introductionsupporting
confidence: 91%
“…Sofue 1995;Morris & Serabyn 1996;Bally et al 2010). In other scenarios, gas within the bar's inner Linblad resonance (∼1 kpc for the Milky Way) is driven inwards by angular momentum transport induced by acoustic instabilities (Montenegro, Yuan & Elmegreen 1999;Kruijssen et al 2014;Krumholz & Kruijssen 2015;Krumholz, Kruijssen & Crocker 2017). Approaching the galactic centre, the galaxy's rotation curve turns from flat to solid body and the inward transport slows down, leading to a buildup of gas.…”
Section: G a L Ac T I C C E N T R E G A S K I N E M At I C P Ro P E Rmentioning
confidence: 99%
“…As noted by , the H69α emission, which predominantly traces young H II regions, is much more uniformly distributed. This intriguing lack of correspondence between the large dense gas reservoir and star formation activity tracers in the CMZ, and the implications of this for our understanding of star formation in other environments, is currently under active investigation Kruijssen et al 2014;Krumholz & Kruijssen 2015;Krumholz et al 2017). …”
Section: A P P E N D I X a : A D D I T I O Na L H O P S Datamentioning
confidence: 99%
“…The complex interplay of energetic processes in the GC allows for different potential answers to this problem of low SFE, but none of these processes alone can explain the discrepancy (Kruijssen et al 2014). A general picture of episodic starbursts in gas rings in galactic centers introduced by Krumholz & Kruijssen (2015) and Krumholz et al (2017) might solve the SFE problem in the particular case of the CMZ and set the framework for another intriguing feature of the GC: a ring-like structure of dust and molecular gas. This structure (see Figure 1 for an overview) is projected onto an infinity (¥) shape that follows several arcs, the most prominent being the so-called "dust ridge" stretching from the massive molecular cloud G0.253+0.016 ("the Brick") to the star-forming region Sgr B2 (Lis et al 1999 , gas is more likely to be on the far side, i.e., behind SgrA * (Bally et al 2010;Molinari et al 2011).…”
Section: Introductionmentioning
confidence: 99%